Research on Satellite Internet Security Simulation Test Technology - Hao LI; Linjie ZHANG; Yifei ZHANG (天地一体化信息网络)
Aiming at the challenges of continuous evolution of large-scale systems, massive attack data management and control, and flexible implementation of diversified test tasks, a system architecture and technical structure based on software-defined network and cloud platform were proposed.Key technologies such as high-fidelity large-scale network element simulation, high concurrent traffic generation, and dynamic choreography of security service chain based on SDN were studied in depth, and solutions were proposed.The experimental results showed that these three technologies were innovative and could be applied to the construction of the integrated simulation test platform.